A clinico-histopathological review of ovarian masses at a tertiary care centre - Fonseca, Michelle N.; J., Madhavi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Ovarian tumours can be seen at all stages of life but they differ in type, being mostly germ cell tumours in childhood, functional cysts in the reproductive age group (up to 45 years) and becoming increasingly malignant towards and after menopause. It also accounts for most prevalent cause of hospital admissions. Methods: This is a retrospective study conducted in the Department of Obstetrics and Gynaecology at a tertiary care hospital in Mumbai from August 2017 to August 2018. All patients with ovarian masses who were surgically managed were included in the study. The data of 30 patients was collected in excel sheet and analyzed by descriptive statistics. Results: Out of the 30 ovarian masses, 50 % were functional cysts, 46.6% were benign ovarian masses and 3.3% were borderline malignant. 46% of tumours were seen in the age group 21-30 years. More than 50 % tumours were seen in parous women. Most common presenting clinical symptom was pain in abdomen irrespective of the type of tumour. Most common complication was haemorrhage in the cyst. Laparoscopy was done in 4 patients and 26 required exploratory laparotomy. Most common surgery performed was unilateral cystectomy for functional ovarian cysts and benign ovarian tumours. Mucinous cystadenoma was the most common benign ovarian tumour, followed by dermoid cyst. Conclusions: Pre-operative diagnostic approach to a patient with ovarian mass includes careful history taking, thorough clinical examination, ultrasound and tumour marker assays in selected cases. Conservative surgery should be the goal to preserve fertility in young patients with ovarian tumours.